Hubungan Nilai Konsolidasi dan Nilai Kuat Tekan Bebas pada Tanah Lempung yang Disubtitusi Material Pasir - Kurniawan, Dedy; Iswan, Iswan; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study was conducted to determine the behavior of reduction and compressive strength in claywhich is substituted with sand material and to see the correlation between the value ofconsolidation and the compressive strength on the soil. Because the clay when getting loadingthere will be a significant reduction in soil that affects the reduction in carrying capacity orcompressive strength of the soil. In this study used clay from the village of Belimbing Sari, Jabungdistrict, East Lampung with the coordinates of 105° 39 '10.74 "T and 5 ° 31' 44.26" S.The research was done by testing on samples without a mixture of clay and the clay soil mixedwith sand with varying amounts of sand mixture of 10%, 20%, and 30%. Testing was conducted ona standard compaction test to find the optimum water content, consolidation testing to find thevalue of the coefficient of consolidation (Cv), compression index (Cc) and coefficient ofcompression (Av) and compressive strength testing are free to seek the compressive strength on thesoil.Based on the results of this study can be seen in the behavior of a mixture of clay and sand withoutonce mixed with sand material that is an increase in the value of the coefficient of consolidation(Cv), a decrease in the value of compression index (Cc) and coefficient of compression (Av) and anincrease in the compressive strength (qu) in the clay soil. Value increases and decreases that occurwithout a mixture of clay and after mixed variations mixture of 10%, 20%, and 30% tend to bestable. From this study it can be concluded that the value of consolidation and strong correlationpress substituted clay with sand material that is smaller then the consolidation of soil compressivestrength will be greater as well.Keywords: Soil Clay, Sand, Consolidation, Soil Compressive Strength